Effects of plyometric jump training on physical performance in female soccer players across the competitive level: a systematic review with meta-analysis of randomized controlled trials - Hernandez-Martinez, Jordan; Coñapi-Union, Bayron; Canales-Canales, Sebastian; Perez-Carcamo, Joaquin; Sanchez-Sanchez, Javier; Sánchez, Mario; Cid-Calfucura, Izham; Vasquez-Carrasco, Edgar; Herrera-Valenzuela, Tomás; Magnani Branco, Braulio Henrique; Valdés-Badilla, Pablo (Frontiers in Physiology, 2025)
This systematic review with meta-analysis aimed to update the analysis of the available body of peer-reviewed randomized controlled trials (RCTs) articles on the effect of plyometric jump training (PJT) on physical performance in female soccer players according to competitive level. Six databases (PubMed, Medline, Collection of Psychological and Behavioral Sciences, CINAHL Complete, Scopus and Web of Science) were searched. The PRISMA, TESTEX, RoB 2, and GRADE instruments were utilized to assess methodological quality and certainty of evidence. Effect sizes (Hedge’s g) for physical performance variables were calculated using both fixed and random-effects models. Subgroup analysis were conducted based on competitive level (amateur/professional), program duration, training frequency, and total number of sessions. The protocol was registered in PROSPERO (code: CRD42025634705). Fourteen RCTs were included, with 149 participants in 15 experimental groups and 139 in 14 control groups. Several meta-analysis were conducted, revealing significant improvements in countermovement jump (p = 0.07; ES = 0.59), squat jump (p = 0.00; ES = 0.76), drop jump (p = 0.01; ES = 1.65), maximum jump power (p = 0.00, ES = 0.85), Illinois test (p = 0.00, ES = 1.15), 20-m shuttle run test (p = 0.13, ES = 1.12), and ball kicking (p = 0.00; ES = 1.30). Subgroup studies revealed that PJT was more effective in professional soccer players than in amateur players (p = 0.03, ES = 0.54). Interventions with fewer than 16 sessions (p = 0.003, ES = 0.52), more than 6 weeks in duration (p = 0.05, ES = 1.42), and fewer than 2 sessions per week (p = 0.005, ES = 0.50) resulted in a significant improvement in countermovement jump. In conclusion, PJT significantly improved jump height, agility, speed lineal and kicking power tests in female soccer players.Systematic Review RegistrationCRD42025634705.